Assessment of proposed dams in reducing flood hazard in Kelantan River basin using hydrodynamic model and geospatial techniques - Maruti@Ezani, Syaza Faiqah (2019)
Flood disaster that struck east coast part of Peninsular Malaysia in 2014 caused damages and fatalities to the affected areas. During this catastrophe, Kelantan state was the most affected by flood which was rated as the worst in Malaysian history. The confluence of two rivers in Kelantan; Galas and Lebir gives high flood magnitudes to the downstream area particularly, Kuala Krai. Kelantan has no structural approach to overcome flood from occurring in this state. To address this problem, Kemubu and Lebir dams were proposed by the Department of Irrigation and Drainage (DID) to be built along Galas and Lebir rivers, as a flood mitigation measure. Development of these two dams has the potential to reduce the flood magnitude. With the availability of advanced technologies, hydrodynamic modelling can be a main tool for researchers to conduct simulation of floods. The research assessed the implementation of the proposed dams at the upstream area to reduce flood hazard in Kelantan using the hydrodynamic modelling approach. These dams were simulated at the upstream area along Galas and Lebir rivers by using the characteristics defined according to the Unit Perancang Ekonomi Negeri Kelantan report. Meanwhile, the flood events with and without these dams were observed at the downstream area particularly in Kuala Krai by simulating the 2014 flood event and different return periods. The Digital Terrain Model (DTM) with 15m spatial resolution was generated by combining the Light Detection and Ranging (LiDAR) and Shuttle Radar Topography Mission (SRTM) data which were then used for the hydrodynamic modelling. The flow hydrograph and water level for 25, 100 and 200-year return periods were generated as input data for initial and boundary conditions. River cross-sections and surface roughness coefficient were also incorporated in the model. The results of maximum velocity and water depth from the hydrodynamic modelling were used to produce flood impulse and flood hazard maps at Kuala Krai. Flood simulation of Kuala Krai with the proposed dams showed that no flood would occur at the downstream based on the discharge input considered. The peak discharge of the floodwater at Kemubu dam decreased from 2,956 m3/s to 142 m3/s after cresting the Kemubu dam spillways. Meanwhile, no discharge was measured at Lebir dam since there was no flood water cresting at the Lebir dam spillways. The storage capacity of the Kemubu and Lebir dams was also measured. The landuse affected by flood at the proposed dams and Kuala Krai area were identified by overlaying the flood extent map with 2013 landuse map obtained from Department of Agriculture (DOA). By having the Kemubu and Lebir dams, the oil palm and forested areas would be the worst affected. Rubber was the most affected landuse at Kuala Krai area. Validation was done by comparing the flood depth at Kuala Krai town obtained from the simulation against field survey data by researchers from Disaster Prevention Research Institute, Kyoto University, Japan and DID. Validation revealed that the average flood depth difference was 3.85m with the Root Mean Square Error (RMSE) value of 4.63m. Based on the findings, it is suggested that a higher accuracy of DTM should be used as the primary input for the flood model and be taken into consideration to improve the RSME value.